Pemikiran Kalam Hassan Hanafi: Rekonstruksi Epistemologi Keilmuan Kalam dan Tantangan Modernitas - Hendri Nadiran (Intizar, 2015)
This paper is a research result which discusses about the thought of Kalam Hassan Hanafi by focusing on the review of its epistemology reconstruction. This research concludes that the basic epistemology of Hassan Hanafi is not solely based on the awareness and western paradigm, but also rooted in the consciousness and traditions of Muslims themselves. This basic epistemology is then applied to reconstruct a new thought. In this case, the reconstruction gives a new meaning and name towards the terms. It is also a part of his great project that includes al-yasar al-islami, turats revitalization and Occidentalism. Further, the judgment on his theology reconstruction that changes the religious terms into mere materials makes the spiritual understanding just become a social, practical and functional agenda.